Karakteristik Massa Katup Limbah dan Tinggi Angkat Terhadap Efisiensi Pompa Hidram 3 Inci - Muhamad Jafri; Nurhayati; Dominggus G. H. Adoe; Gusnawati (Universitas Negeri Gorontalo, 2020)
The research aim was to analyze the effect of the wastevalve mass and the deliver head on the hydram pump efficiency. The method used is the experimental method for the 3-inch hydram pump specimen, then analyzed using mathematical equations in the theory of the hydram pump on the head loss and pump efficiency. The data measured are the inflow, wastewater, and hydram pump outflow. The independent variables in this study were the wastevalve mass, namely 1.5 kg, 2.0 kg, 2.5 kg, and 3.0 kg, and deliver head, namely 3 m, 5 m, and 7 m. The results showed that the wastevalve mass and deliver head an effect on the hydram pump efficiency. The highest efficiency of the hydram pump is at a deliver head of 5 m with 1.5 kg of wastevalve mass, which is 60.60%. Meanwhile, the lowest hydram pump efficiency occurs at a deliver head of 7 m with 3.0 kg of wastevalve mass, which is 27.10%.